Analisis Makna Label Tasya Farasya Approved - Fitri Nuraeni; Weni A. Arindawati; Tri Widiya Budhiharti (Fakultas Ilmu Sosial dan Ilmu Poliitik Universitas Ichsan Gorontalo, 2026)
This study aims to explore the meaning contained in the Tasya Farasya Approved label through Roland Barthes' semiotic approach. Data was collected through direct observation of the content published by Tasya Farasya on social media platforms and a literature review of related studies. This label does not only function as a visual complement but is part of the visual communication strategy used by Tasya Farasya, a well-known beauty influencer in Indonesia, to build a credible, authoritative, and convincing image for the products she endorses. This research is qualitative in nature and uses a semiotic analysis approach. Based on the results of denotative analysis, the label consists of visual elements such as the text